(untitled) (Dhaka University Journal of Science, 2023)
A number of complex compounds of aceclofenac with different first-row transition metal ions like Co(II), Mn(II), Ni(II), Cu(II), and Zn (II) were synthesized in an aqueous medium and characterized on the basis of their UV-Visible, FTIR spectra, elemental (C, H, N) analyses, and metal estimation data. Thermogravimetric analysis (TGA) was also done. Conductivity measurement and magnetic susceptibility measurement were also done to have information about the electrolytic behavior of the compounds and oxidation states of the central metal atoms respectively. Dhaka Univ. J. Sci. 71(2): 153-159, 2023 (July)